Análise de fatores determinantes da estrutura de capital pela metodologia CAMEL - estudo de caso do Banco Industrial e Comercial da China (ICBC) - Oliveira, Luana Lopes de (2020)
The banks perform a leading role to the operation of the economic systems and development of the countries. The way they realize the fundraising to their capital structure can affect significantly their results. Generally, these institutions enable a greater third-party capital participation, mainly higher levels customer deposits as it was considerate one of the ways of attracting less costly, creating ideals conditions to the results leverage. When considering the atypical structure capital of the banking industry with regard to the other economy sectors, it was chosen to analyze the relation between determinant factors and theories of the capital structure by Camel methodology in a corporate governance environment. The obtained results, partly, provide support to the Static Tradeoff, Pecking Order e Equity Market Timing theories assumptions, that emphasize indirectly the effective management of the financial resources picked up in the market, i.e. raising resources always taking into account the benefits of the favorable accounting-financial performance. Specifically in the ICBC case, it was found favorable performance indicators in the Camel index predominance, that possibly they have adjusted their capital cost downward, benefiting the financial resources restitution in the capital structure. In relation to the determinant factor of the “risk” capital structure, there was a comfort zone or certainty for market players, considering that the high leverage has generated, in contrast, operating cash flows more than enough to attend the return expectation of the capital suppliers and an appropriate capital maintenance to the risk much higher than market benchmark (11%). As a result, it may even admit that the financial resources restitution in the capital structure was conducted in favorable conditions compatible with the credit risk reduction and ICBC capital cost. Regarding to the capital structure determinant factor “cost-effectiveness/profitability”, the maintenance of the favorable situation in the period, emphasized by Return on Net Equity, Net Operating Cash Flow, Operating Profit and Price/Profit indices also suggests that the financial resources restitution in the capital structure was carried out in favorable conditions compatible with the credit risk reduction and ICBC capital cost